2022
DOI: 10.1038/s41598-022-09252-3
|View full text |Cite
|
Sign up to set email alerts
|

Selective etching of silicon nitride over silicon oxide using ClF3/H2 remote plasma

Abstract: Precise and selective removal of silicon nitride (SiNx) over silicon oxide (SiOy) in a oxide/nitride stack is crucial for a current three dimensional NOT-AND type flash memory fabrication process. In this study, fast and selective isotropic etching of SiNx over SiOy has been investigated using a ClF3/H2 remote plasma in an inductively coupled plasma system. The SiNx etch rate over 80 nm/min with the etch selectivity (SiNx over SiOy) of ~ 130 was observed under a ClF3 remote plasma at a room temperature. Furthe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The etching rate of SiO x reached a maximum of 940 nm min −1 at 2.5 slm and decreased to 550 nm min −1 with increasing F H from 2.5 to 5 slm. The etching rate of SiN x was lower than that of SiO x , which is different from the conventional dry etching using F-based plasma [18][19][20][21].…”
Section: Effect Of H 2 Flow Rate On Etching Behaviormentioning
confidence: 63%
See 2 more Smart Citations
“…The etching rate of SiO x reached a maximum of 940 nm min −1 at 2.5 slm and decreased to 550 nm min −1 with increasing F H from 2.5 to 5 slm. The etching rate of SiN x was lower than that of SiO x , which is different from the conventional dry etching using F-based plasma [18][19][20][21].…”
Section: Effect Of H 2 Flow Rate On Etching Behaviormentioning
confidence: 63%
“…The obtained activation energies were small, comparable, and negative. Several studies on plasma dry etching of SiO x and SiN x films reported that etching rate increased with temperature [10,12,[18][19][20]37]. Meanwhile, the etching rate of Si by H 2 plasma is known to decrease with rising substrate temperature over approximately 70 • C [38].…”
Section: Effects Of Stage Temperature On Etching Behaviormentioning
confidence: 99%
See 1 more Smart Citation